Optimization of Sentinel Lymph Node Imaging Methodology Using Anionic Liposome and Hyaluronidase - Yu Sakurai; Miho Suzuoki; Masaki Gomi; Hiroki Tanaka; Hidetaka Akita (MDPI AG, 2021)
The sentinel lymph node (SLN) is the first lymph node into which lymphatic fluid from tumor tissues flows. The development of a highly sensitive probe for detecting SLNs is desired for the lymph node dissection through intraoperative biopsy. We have previously shown that anionic liposomes tend to accumulate in lymph nodes and that macrophage uptake of liposomes contributes to their accumulation. In the present study, we found that among anionic lipids, phosphatidylserine (PS)-containing liposomes were substantially taken up by macrophages. We identified a new lipid composition to improve the SNL-selectivity of liposome accumulation based on Design-of-Experiment. The optimized PS-containing particles were more selectively accumulate to SLN lymph nodes than existing imaging agents indocyanine green. These results indicate the effectiveness of PS-containing anionic particles in SLN imaging.